The Competition between Competition Rules - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 1999)
Open borders imply systems competition. This paper studies the implications of systems competition for the national co mpetition rules. It is shown that an equilibrium where all countries retain their antitrust laws does not exist, since abolishing this law makes it possible for a single country to establish a cartel that successfully appropriates foreign business profi t s. Instead of such an equilibrium, a deregulation race is likely to emerge in which all but the last country repeal their antitrust laws. The deregulation race results in a chain of Stackelberg leadership positions taken over by national cartels that rend ers lower profits and higher consumer rents than would have been the case with harmonization of the antitrust laws.
Keywords: 330